2016
DOI: 10.1108/ijpcc-01-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

TDAS: a touch dynamics based multi-factor authentication solution for mobile devices

Abstract: The use of mobile devices in handling our daily activities that involve the storage or access of sensitive data (e.g. on-line banking, paperless prescription services, etc.) is becoming very common. These mobile electronic services typically use a knowledge-based authentication method to authenticate a user (claimed identity). However, this authentication method is vulnerable to several security attacks. To counter the attacks and to make the authentication process more secure, this paper investigates the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…5, by inputting one key, two time-data values are collected at down and up. With this collected data, we can calculate DT feature [48], [49] which denotes the duration user touches the screen; by subtracting time-down which represents the time occurred down from time-up which represents the time occurred up. The formula in Fig.…”
Section: ) Timementioning
confidence: 99%
“…5, by inputting one key, two time-data values are collected at down and up. With this collected data, we can calculate DT feature [48], [49] which denotes the duration user touches the screen; by subtracting time-down which represents the time occurred down from time-up which represents the time occurred up. The formula in Fig.…”
Section: ) Timementioning
confidence: 99%
“…Teh et al [75] – ‘TDAS: a touch dynamics based multi‐factor authentication solution for mobile devices’ . In this paper, the authors propose to implement the use of touch dynamics into a PIN‐based authentication system.…”
Section: Papers In Detailmentioning
confidence: 99%
“…The paper (Teh et al 2016b) reported an experiment carried out to collect a touch dynamics dataset from a group of subjects with a wider age range than those described above. In their experiments, five timing feature and a spatial feature were extracted from the input samples of the dataset, and, for each extracted feature, a reference template is created.…”
Section: Related Workmentioning
confidence: 99%